Allocation, externalities, and the fair division approach: an experimental study - Torsten Weiland (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We experimentally investigate four allocation mechanisms - all based on the fair division approach, with varying bid elicitation methods and price rules - in terms of their allocation efficiency, distributional effects, and regularities in individual bidding behavior. In a repeated design, an indivisible good is assigned that generates profits for its owner but, at the same time, exerts negative externalities on the non-acquiring bidders. Both the bidders'; valuations of the good and their potentially incurred damages are stochastic and denote private information, inciting strategic bidding and complicating an efficient allocation. Indeed, observed bidding is dominated by strategic reporting which, however, only marginally diminishes efficiency. One particular allocation mechanism, relying on sparse information elicitation and the first-price rule, is found to yield economically superior results to both more complex and second-price based allocation mechanisms.
Keywords: C92; D44; D62; L14; 330; Allocation; auction; fair division; externalities; experiment; Auktion; Allokation; Gerechtigkeit; Externer Effekt; Test